2019
DOI: 10.1111/pce.13602
|View full text |Cite
|
Sign up to set email alerts
|

Roles of plant volatiles in defence against microbial pathogens and microbial exploitation of volatiles

Abstract: Plants emit a large variety of volatile organic compounds during infection by pathogenic microbes, including terpenes, aromatics, nitrogen-containing compounds, and fatty acid derivatives, as well as the volatile plant hormones, methyl jasmonate, and methyl salicylate. Given the general antimicrobial activity of plant volatiles and the timing of emission following infection, these compounds have often been assumed to function in defence against pathogens without much solid evidence. In this review, we critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
166
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(172 citation statements)
references
References 146 publications
6
166
0
Order By: Relevance
“…A considerable number of metabolic pathways related to both BACs and the selected scaffolds were also detected. However, specific pathways were found to be associated with these scaffolds, mainly due to the different roles of the proteins encoded by these identified CDSs and because these pathways were already reported as being associated with plant responses to different pathogens 123,[128][129][130][131][132][133][134][135] , further corroborating our findings. The indication of possible mutation events in these regions provides evidence of differences in protein expression and phenotypic characteristics.…”
Section: Discussionsupporting
confidence: 89%
“…A considerable number of metabolic pathways related to both BACs and the selected scaffolds were also detected. However, specific pathways were found to be associated with these scaffolds, mainly due to the different roles of the proteins encoded by these identified CDSs and because these pathways were already reported as being associated with plant responses to different pathogens 123,[128][129][130][131][132][133][134][135] , further corroborating our findings. The indication of possible mutation events in these regions provides evidence of differences in protein expression and phenotypic characteristics.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported positive correlations between plant volatile terpenoid emissions and resistance to plant pathogens 57 . For example, downy mildew (Plasmopara viticola )-resistant grapevine genotypes emitted significantly more monoterpenes and sesquiterpenes than susceptible genotypes 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Volatile compounds released from host plants play an important role in plant defense against microbial pathogens (Hammerbacher et al, 2019). Allium species are well-known to produce many volatile organosulfur compounds, which contribute to the unique smell and taste of these plant species (Nandakumar et al, 2018;Marrelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%